Distribution and perinatal transmission of bacterial vaginal infections in pregnant women without vaginal symptoms. (May 2014) - Hahn, Ho-Suap; Lee, Ki-Heon; Koo, Yu-Jin; Kim, Soon-Gyu; Rhee, Jee Eun; Kim, Moon Young; Hwang, Soo-Jin; Lee, Jae Ho; Lee, In-Ho; Lim, Kyung-Taek; Shim, Jae-Uk; Kim, Tae-Jin
Abstract Background: We evaluated the distribution and vertical transmission of bacterial vaginal infections in asymptomatic pregnant women. Methods: We performed multiplex PCR on secretions collected on cervical swabs from pregnant women at over 36 weeks of gestation and on oral secretions collected from their neonates immediately after delivery. We detected sexually transmitted infections (STIs) with the following 6 species: Trichomonas vaginalis, Mycoplasma hominis, Mycoplasma genitalium, Chlamydia trachomatis, Neisseria gonorrhoeae, and Ureaplasma urealyticum. Results: Infectious agents were detected in 64 of 455 pregnant women (14.1%) and in 11 neonates (2.4%). The rate of vertical transmission was 17.2% and all the infectious agents detected in neonates were concordant with those found in their mothers. U. urealyticum was the most frequently detected in the maternal genitalia, followed by M. hominis. Women who were in labor for a longer period of time had a higher risk of vertically transmitting STI agents to their neonates. Conclusions: Vertical transmission of bacterial STIs from mothers to their infants is possible at delivery and influenced by the duration of labor. STIs should be diagnosed in pregnant women to prevent vertical transmission from the mother to the infant at the time of delivery.